Determinants of treatment non-attendance among those referred to primary mental health care services in Western Sydney, Australia: a retrospective cohort study. Issue 10 (26th October 2020) - Munasinghe, Sithum; Page, Andrew; Mannan, Haider; Ferdousi, Shahana; Peek, Brendan
Abstract : Objectives: Recommendations of the recent mental health reforms provided an opportunity to implement regional approaches to service provision through Primary Health Networks. This study is designed to identify the determinants of sociodemographic, diagnostic and referral-level factors and first treatment session non-attendance among those referred to primary mental health care (PMHC) services in Western Sydney, Australia. Design: This study used routinely collected retrospective PMHC data between July 2016 and December 2018. Setting: The study was based on a geographical catchment that covers four local government areas of Blacktown, Parramatta, Cumberland and Hills Shire in Western Sydney, Australia. Participants: All individuals 5 years of age or older referred to PMHC services. Primary outcome measure: First treatment session non-attendance, following a referral to receive psychological treatments. Results: There were 9158 referrals received for 8031 clients, with 1769 (19.32%) referrals resulting in non-attendance to the first treatment session. Those with younger age (ORs ranging from 1.63 to 1.92), substance use (OR=1.55, 95% CI 1.17 to 2.06), poor English proficiency (OR=1.64, 95% CI 1.23 to 2.20), lower socioeconomic status (OR=1.57, 95% CI 1.34 to 1.83), psychotropic medication use (OR=1.20, 95% CI 1.06 to 1.36), and a referral by a social worker (OR=2.04, 95% CI 1.36 to 3.05), allied health (OR=1.49, 95% CI 1.03 to 2.16) or other professional (OR=1.72, 95% CI 1.30 to 2.29) were associated with a higher likelihood of first treatment session non-attendance. Those with a risk of suicide, who mainly speak a language other than English, and a previous use of PMHC services were more likely to attend their first treatment session. Conclusion: Youth-specific treatment approaches, behavioural engagement strategies, facilitation of transport services for those live in deprived regions and improvements in capacity for mental health training among allied health professionals are areas of focus for primary care service and policy responses.